2019
DOI: 10.2147/bctt.s174298
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of BP-C1 in metastatic breast cancer: a Phase II, randomized, double-blind, and placebo-controlled Thai multi-center study

Abstract: AimsThe aim of this study was to compare the efficacy and tolerability of BP-C1 vs equal-looking placebo in metastatic breast cancer.Materials and methodsA randomized, double-blind, placebo-controlled multi-center study with a semicross-over design was performed. Sixteen patients received daily intramuscular injection of 0.035 mg/kg bodyweight of BP-C1 and 15 patients received equal-looking placebo for 32 days. After 32 days, the placebo patients crossed to BP-C1 with the last observation in the placebo period… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…2021, 11, x FOR PEER REVIEW 2 of 9 metastatic breast carcinoma (ClinicalTrials.gov identifiers: NCT04298333, NCT03789019, NCT03603197, NCT02783794 and NCT01861509). The trials indicated that prolonged intramuscular administration of BP-C1 resulted in the stabilisation of tumour growth and normalised haematological parameters [10,11]. Chemical characterisation of the ligninderived BP-Cx-1 ligand was previously reported [8].…”
Section: Introductionmentioning
confidence: 90%
“…2021, 11, x FOR PEER REVIEW 2 of 9 metastatic breast carcinoma (ClinicalTrials.gov identifiers: NCT04298333, NCT03789019, NCT03603197, NCT02783794 and NCT01861509). The trials indicated that prolonged intramuscular administration of BP-C1 resulted in the stabilisation of tumour growth and normalised haematological parameters [10,11]. Chemical characterisation of the ligninderived BP-Cx-1 ligand was previously reported [8].…”
Section: Introductionmentioning
confidence: 90%
“…Controlled clinical studies of BP-C1 against Stage IV metastatic breast cancer have shown promising effect both in humans and in dogs. [8][9][10][11][12] The treatment has been found very well tolerated and only few and mainly mild AE has been reported. 13 A pancreatic cancer case study with BP-C2 shows promising, and interesting results related to strengthening of the immune system.…”
Section: Introductionmentioning
confidence: 98%